2021
DOI: 10.1016/j.celrep.2021.109394
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of CCNK/CDK12 is a druggable vulnerability of colorectal cancer

Abstract: Highlights d A screen for inhibitory compounds of colorectal cancer spheroids identifies NCT02 d NCT02 acts as a molecular glue and induces degradation of CCNK and CDK12 d Knockout of CCNK or CDK12 and targeted CCNK degradation decrease tumor growth d TP53 deficiency and consensus molecular subtype 4 predict sensitivity to NCT02

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 61 publications
0
40
0
Order By: Relevance
“…Examples here include the approved IMiD class, which relies on CRBN to degrade IKZF1/IKZF3 (refs 4 , 5 ) via a molecular glue mechanism; sulfonamides previously in clinical trials 81 , 82 that have since been shown to use DCAF15 to degrade RBM39 (refs 25 , 27 , 29 ), also via a molecular glue mechanism elucidated by elegant structural biology in recent work by multiple groups 26 , 28 , 83 ; and, most recently, a unique class of cyclin-dependent kinase 12 (CDK12) inhibitors, exemplified by CR8, which, unexpectedly, has been shown to directly co-opt DDB1 as an E3 ligase for the degradation of cyclin K (CCNK) 84 86 . In fact, not only CR8, but four separate classes of compounds, each discovered by a different screening method, were found to have molecular glue-like properties in potentiating the interaction of DDB1 and CDK12, resulting in CCNK degradation 84 87 . These findings suggest that many more compounds, including those approved or already in the clinic, could have a hitherto overlooked degrader contribution to their mechanism of action.…”
Section: Outlook For the Next 20 Years Of Tpdmentioning
confidence: 99%
“…Examples here include the approved IMiD class, which relies on CRBN to degrade IKZF1/IKZF3 (refs 4 , 5 ) via a molecular glue mechanism; sulfonamides previously in clinical trials 81 , 82 that have since been shown to use DCAF15 to degrade RBM39 (refs 25 , 27 , 29 ), also via a molecular glue mechanism elucidated by elegant structural biology in recent work by multiple groups 26 , 28 , 83 ; and, most recently, a unique class of cyclin-dependent kinase 12 (CDK12) inhibitors, exemplified by CR8, which, unexpectedly, has been shown to directly co-opt DDB1 as an E3 ligase for the degradation of cyclin K (CCNK) 84 86 . In fact, not only CR8, but four separate classes of compounds, each discovered by a different screening method, were found to have molecular glue-like properties in potentiating the interaction of DDB1 and CDK12, resulting in CCNK degradation 84 87 . These findings suggest that many more compounds, including those approved or already in the clinic, could have a hitherto overlooked degrader contribution to their mechanism of action.…”
Section: Outlook For the Next 20 Years Of Tpdmentioning
confidence: 99%
“…Interestingly, by screening a small-molecule library against primary colorectal cancer (CRC) heterogeneous spheroids, Dieter et al found a compound named NCT02 with a chemical structure similar to HQ461 ( Figure 4 A) that acts as an MG degrader to induce ubiquitination of cyclin K (CCNK) and proteasomal degradation of both CCNK and its partner CDK12 [ 28 ].…”
Section: Molecular Glues For Cancer Treatmentmentioning
confidence: 99%
“…After 2 h incubation, fluorescence intensity was measured using a Tecan reader. Alternatively, the ATP lite luminescence assay (Perkin Elmer, Waltham, MA, United States) was used as described before [ 61 ]. For combination treatment of Afatinib (MedChemExpress, Monmouth Junction, NJ, United States) with Vemurafenib, a fixed Vemurafenib dose was used and 20-point dilutions of Afatinib (50 µM to 95 pM) were performed as indicated in the respective figure legends.…”
Section: Methodsmentioning
confidence: 99%